2018
DOI: 10.1080/09593985.2018.1457747
|View full text |Cite
|
Sign up to set email alerts
|

The validity and reliability of the ADL-Glittre test for children

Abstract: The TGlittre-P proved to be a valid and reliable assessment of the functional capacity of healthy children aged 6 to 14 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 24 publications
1
43
2
9
Order By: Relevance
“…Likewise, Martins observed that even healthy children reported a higher perception of effort at the end of the 6MWT versus TGlittre‐P, although both tests induced a similar cardiorespiratory responses. The authors explain that the more dynamic nature of TGlittre‐P activities, compared to the monotonous walk of 6MWT, may spark a sense of play in children and motivate them.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Likewise, Martins observed that even healthy children reported a higher perception of effort at the end of the 6MWT versus TGlittre‐P, although both tests induced a similar cardiorespiratory responses. The authors explain that the more dynamic nature of TGlittre‐P activities, compared to the monotonous walk of 6MWT, may spark a sense of play in children and motivate them.…”
Section: Discussionmentioning
confidence: 87%
“…The adapted version for the Glittre‐ADL for the pediatric population (TGlittre‐P) was applied . The test consists of the child carrying a backpack weighing between 0.5 and 2.5 kg according to their individual mass for 5 laps around a specific circuit.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations